Gastroparesis and botulinum toxin. (13th March 2011) - Rameshshanker, R; Smith, L A; Southern, P; Whitelaw, D; Beckett, C
Abstract : Introduction: Gastroparesis is defined as delayed gastric emptying. The common causes are diabetes, post surgical, idiopathic. It s management poses a significant challenge in the practice of Gastroenterology. It is defined as resistant when usual conventional measures (Dietary modification, antiemetics, prokinetics, etc) fail to control the symptoms. We chose the resistant cases who underwent Botox (botulinul toxin A) treatment to the pyloric region. Methods: It is a retrospective analysis of patients with resistant gastroparesis during Dec 2005–June 2010 in our District Hospital. Their OGD reports, case notes clinic letters were analysed. Results: Total no of patients 21, Male 06, Female 15 (M:F 2:5). Age range 23–76 years. Mean age 47.8 years. Median and mean follow-up 2 years.81% (17) of them were diabetic, others were idiopathic cases. All of them had vomiting, 60% of them had bloating and early satiety as their presenting symptoms. All had antiemetics and prokinetics, 65% had erythromycin and 20% had amitriptyline. All of them had intrapyloric Botox (200 units) using 23G, 8 mm needle. Treatment repeated when symptoms recur. 61.8% showed good response to botox, 19% showed no response. Mean duration of response was 4.2 months.72% of diabetic gastroparesis showed good response. Significant improvement in GCIS (Gastroparesis Cardinal Symptom Index) noted in diabetic group (p < 0.05).62% of diabetic gained weight and 50% insulin requirements increased post-treatment. Conclusion: This is probably the first published study with longer follow-up period from UK (mean 2 years, maximum 3.8 years). More beneficial in diabetic gastroparesis. Less effective in idiopathic group. Failures may respond to gastric pacing.